2011
DOI: 10.2319/021111-101.1
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of photocatalytic titanium oxide surface modified stainless steel orthodontic brackets for antiadherent and antibacterial properties against Lactobacillus acidophilus

Abstract: Surface modification of orthodontic brackets with photocatalytic TiO(2) can be used to prevent the accumulation of dental plaque and the development of dental caries during orthodontic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
55
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 13 publications
2
55
0
Order By: Relevance
“…Shah et al used this method to apply photocatalytic TiO 2 to stainless steel orthodontic brackets in order to assess the antiadherent and antibacterial properties of such compounds against Lactobacillus acidophilus. Photocatalytic TiO 2 demonstrated antibacterial and antiadherent properties; therefore, these authors also recommended it as a surface modification material to prevent developing dental plaque during active orthodontic treatment [70]. Ozeki et al [71] coated NiTi alloy plates with hydroxyapatite, alumina, and titanium using this method to alleviate the effects of nickel allergy from NiTi alloy implants.…”
Section: Radiofrequency (Rf) Magnetron Sputtering Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shah et al used this method to apply photocatalytic TiO 2 to stainless steel orthodontic brackets in order to assess the antiadherent and antibacterial properties of such compounds against Lactobacillus acidophilus. Photocatalytic TiO 2 demonstrated antibacterial and antiadherent properties; therefore, these authors also recommended it as a surface modification material to prevent developing dental plaque during active orthodontic treatment [70]. Ozeki et al [71] coated NiTi alloy plates with hydroxyapatite, alumina, and titanium using this method to alleviate the effects of nickel allergy from NiTi alloy implants.…”
Section: Radiofrequency (Rf) Magnetron Sputtering Methodsmentioning
confidence: 99%
“…This collision creates a momentum transfer and ejects atomically sized particles from the target. These particles are deposited as a thin film onto the surface of substrates [70]. Shah et al used this method to apply photocatalytic TiO 2 to stainless steel orthodontic brackets in order to assess the antiadherent and antibacterial properties of such compounds against Lactobacillus acidophilus.…”
Section: Radiofrequency (Rf) Magnetron Sputtering Methodsmentioning
confidence: 99%
“…It has also been demonstrated that Listerine and Corsodyl mouth rinses inhibited biofilm formation on orthodontic brackets. 6 Shah et al 7 reported that stainless steel orthodontic brackets modified with a photocatalytic titanium oxide (TiO 2 ) coating resulted in reduced bacterial adherence and less biofilm accumulation. The prevention of biofilm formation has been studied extensively; however, according to recent studies, the prevalence of WSLs remains high.…”
Section: Introductionmentioning
confidence: 99%
“…Shah et al 7) modified the surface of steel and TiO2 orthodontic brackets by using UV radiation treatment, and these brackets had a bactericidal effect on Lactobacillus acidophilus. However, the absorption band of TiO 2 is limited within the UV region to a wavelength of less than 387 nm, and it can only utilize UV light, which constitutes only 5% of sunlight.…”
Section: Introductionmentioning
confidence: 99%